Dental caries and quality of life among primary school children - Tiarma Talenta Theresia; Lia Hapsari Andayani; Abdul Gani Soulissa; Sri Lestari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Oral health problems are still commonly found in Indonesia because there is a prevailing belief that dental issues do not cause death and, therefore, are not a priority. The prevalence of dental caries in children aged 10–14 years in Jakarta is 37.2%. Untreated dental caries can have various negative effects. Persistent pain may lead to difficulty chewing and sleep disturbances, affecting quality of life and productivity. Purpose: This study aimed to assess the impact of caries on oral health in primary school students in West Jakarta. Methods: The study was conducted in seven public primary schools in West Jakarta between March 2024 and August 2024. Oral examinations and questionnaire surveys were completed by all students from the fourth to sixth grades, with a total sample size of 869 students. In this study, caries was the dependent variable, and the independent variable was oral health-related quality of life (OHRQoL). Data analysis involved bivariate analysis using the Spearman correlation test. Results: There is a significant relationship between dental caries and OHRQoL (p = 0.01). Questions that are statistically related to caries were mostly found in the socio-emotional well-being dimension. Conclusion: This study demonstrates a correlation between dental caries and OHRQoL, indicating that a higher number of dental caries is associated with poorer quality of life.